Hubungan iklim sekolah dan disiplin pelajar tingkatan empat - Mohammad Junaidi, Harun (2010)
The idea of this research is to observe school whether influences and effect towards disciplinary problems among the student. The studies involve four aspects which are school administration, infrastructure, learning and teaching also teachers. In order to address the issues, 169 of form four students from Alor Setar Vocational Tread Secondary School in Kedah Darulaman were identified as a respondent. A set of questionnaire consisting of two parts namely the background of the respondent and 30 statements were distributed to the respondent. The finding and hypothesis were analyzed by using SPSS software (Statistical Package for Social Science - Version 12.0) in order to get the best statistical technique in interpreting the results. The data were analyzed into percentage and frequency from which were then being categorized into five category of achievement levels. The correlation test - result shows that school administration aspects, learning and teaching also teachers score medium level while infrastructure aspect is weak. As a result the implications of school whether influences and effect on the disciplinary matter were suggested through the findings while the limitation of study also identified